Present and future of personalized medicine in adult genitourinary tumors. (May 2015) - Ciccarese, Chiara; Santoni, Matteo; Massari, Francesco; Cheng, Liang; Lopez-Beltran, Antonio; Scarpelli, Marina; Conti, Alessandro; Tortora, Giampaolo; Cascinu, Stefano; Montironi, Rodolfo
ABSTRACT : The development of targeted agents has completely revolutionized the therapeutic scenario of genitourinary tumors. However, no biomarkers of tumor response or patient tolerability have been validated so far, and the selection of patients who may benefit from these approaches is still empirical. Significant advances in genomic sequencing and molecular characterization of these tumors have allowed identification of complex genomic abnormalities, thus increasing our knowledge on cancer biological landscapes and paving the way to the development of personalized strategies based on the patient's genomic and cancer's molecular profiles. This review is an overview of recent findings and emerging individualized therapies in patients with prostate, renal and bladder cancer, focusing on the promises and limitations of this approach in this setting.